2013
DOI: 10.1016/j.bone.2012.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid plays a protective role for bone loss in peri- and postmenopausal women: A longitudinal study

Abstract: Bone mineral density 23Bone loss 24 Uric acid 25 Body composition 26 Fat mass 27Objective: Oxidative stress has been linked to osteoporosis. Serum uric acid (UA), a strong endogenous anti-28 oxidant, has been associated with higher bone mineral density (BMD), lower bone turnover and lower prev-29 alence of fractures in a large cross-sectional study of men. Whether this relationship is present in women and 30 how UA relates to changes in BMD longitudinally has not been examined.31 Methods: A sample of 356 peri-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
92
3
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(108 citation statements)
references
References 50 publications
9
92
3
2
Order By: Relevance
“…An association with incident osteoporotic fractures has also been recently reported in Korean men over 50 years old (8), and older men enrolled in the Osteoporotic Fractures in Men (MrOS) study (9). Similar results have been published in peri-and postmenopausal women (10)(11)(12). However, recent data from NHANES do not support a positive association between serum uric acid and BMD (13).…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…An association with incident osteoporotic fractures has also been recently reported in Korean men over 50 years old (8), and older men enrolled in the Osteoporotic Fractures in Men (MrOS) study (9). Similar results have been published in peri-and postmenopausal women (10)(11)(12). However, recent data from NHANES do not support a positive association between serum uric acid and BMD (13).…”
Section: Introductionmentioning
confidence: 52%
“…Furthermore, a relationship between ROS or low serum levels of antioxidants and male osteoporosis has been pointed out (6). Nevertheless, there are few reports analyzing the role of uric acid levels in patients with osteoporosis (7)(8)(9)(10)(11)(12)(13). Nabipour et al (7), found for the first time, that higher serum uric acid levels were related to higher bone mineral density (BMD), and lower prevalence of vertebral and nonvertebral fractures in older men.…”
Section: Introductionmentioning
confidence: 97%
“…Several studies found that higher serum urate (which is a major risk factor for gout) is associated with higher bone mineral density and a lower risk of fracture [10][11][12][13][14]; one recent study showed no relationship between serum urate and fracture rates in older people [21], another recent study found that higher urate was associated with higher fracture rates in men [22]. Gout, ascertained by any use of allopurinol in a large Danish registry, was associated with higher fracture rates in men but not women [23].…”
Section: Discussionmentioning
confidence: 99%
“…ADP) by xanthine oxidase, it may also indirectly modulate the impact of ADP on purinergic signalling systems. However, any relationship between allopurinol use and fracture is likely to be complex; recent observational data suggest that elevated circulating urate levels are associated with higher bone mineral density and lower fracture risk [10][11][12][13][14], possibly due to antioxidant effects of urate itself. Hence analyses of the effect of allopurinol on fracture risk need to try and separate the effect of gout (a consequence of hyperuricemia) from gout treatment (allopurinol).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, another cross-sectional study done in female subjects also revealed that uric acid has protective role in bone mineral density. A very recent study done by Makovey J et al, revealed that women with higher UA levels had significantly higher absolute BMD measures at all skeletal sites 36 . Therefore, higher serum UA levels appear to be protective for bone loss in periand postmenopausal women and this relationship is not affected by changes in body composition measures 36 .…”
Section: Uric Acid and Bone Mineral Densitymentioning
confidence: 91%